Equilibrium, DNA Cleavage and Antimicrobial Studies of Cu(II) and Zn(II) Complexes with Novel 1-Propionyl-4-methyl-3-thiosemicarbazide - Jyothi, P. Nirmala; Sireesha, B. (Asian Journal of Chemistry, 2019)
Cu(II) and Zn(II) metal complexes with novel Schiff base 1-propionyl-4-methyl-3-thiosemicarbazide (PMTSC) were synthesized and characterized by LC-MS, IR, 1H NMR (D2O exchangeable), 13C NMR and UV-visible spectra, ESR, TGA, molar conductance and magnetic susceptibility measurements. The spectro-analytical studies revealed the composition of complexes as ML2 for Cu(II)-PMTSC and Zn(II)-PMTSC complex. The proton-ligand dissociation constant and metal-ligand formation constants of PMTSC with Zn(II) have been determined in 70 % (v/v) DMF-water medium at 0.1M (KNO3) ionic strength and 303 K using potentiometric Irving-Rossotti titration technique. The results revealed that PMTSC acts as monobasic ligand by releasing proton from amide via enol form and forms 1:2 (Zn-L) complex in solution. The cleavage of plasmid pBR322 DNA without any additives was monitored by gel electrophoresis and these complexes exhibited hydrolytic cleavage of plasmid DNA. The antibacterial activity of the Schiff base and its Cu(II) and Zn(II) complexes were tested against Gram-positive and Gram-negative bacteria.